DIASPORIC CITIZENSHIP: SLAVERY, IDENTITY AND KINSHIP IN YAA GYASI’S HOMEGOING - Addei, Cecilia; Annin, Felicia (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
Homegoing, is the debut novel of Yaa Gyasi, a Ghanaian/American author. As such, the novel belongs to tradition of writings referred to as diasporic literature. This study explores how Yaa Gyasi, even though did not experience slavery, revisits this subject of slavery as a way of continuing the tradition of slave narratives like that of Frederick Douglas and Harriet Jacobs who experienced slavery. The study explores the representation of slavery in the novel, bringing out how slavery broke African kinship ties and left the characters in a form of identity crisis. This study argues that the novel is a representation of loss of kinship ties and identity and the search for same.